2020
DOI: 10.1016/j.ccell.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Cancer Research and Medicine with Single-Cell Genomics

Abstract: Single-cell sequencing (SCS) has impacted many areas of cancer research and improved our understanding of intratumor heterogeneity, the tumor microenvironment, metastasis, and therapeutic resistance. The development and refinement of SCS technologies has led to massive reductions in costs, increased cell throughput, and improved reproducibility, paving the way for clinical applications. However, before translational applications can be realized, there are a number of logistical and technical challenges that mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
168
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 147 publications
0
168
0
Order By: Relevance
“…Pr 0 (x) is the probability of observing the true genotype x : (6) and Pr 1 (x, y) is the probability of observing a genotype y with a d(x, y) of 1 from the true genotype x :…”
Section: Single-cell Genotype Error Modelmentioning
confidence: 99%
“…Pr 0 (x) is the probability of observing the true genotype x : (6) and Pr 1 (x, y) is the probability of observing a genotype y with a d(x, y) of 1 from the true genotype x :…”
Section: Single-cell Genotype Error Modelmentioning
confidence: 99%
“…Since scRNA-seq technology is still an evolving field requiring constant improvement in technologies starting from source of tissues to dissociation protocols, sequencing techniques, and bioinformatics tools (Lim et al, 2020), it is likely that clusters that we identified here will undergo further refinement in the future. Thus, it is appropriate to compare what has been done in the past to the current data.…”
Section: Complexities In Breast Epithelial Cell Types; Past and The Pmentioning
confidence: 99%
“…Since normal tissue itself is composed of multiple cell types, fine mapping of these cell types and identifying potential cancer vulnerable cell population in normal tissues would aid in identifying and characterizing organ-specific cell-of-origin of cancers. Recent advances in single cell techniques including scRNA-seq, sc-Epigenetics, scDNA-seq and scProteomics-atlas are enabling further refinement of cell types within normal and diseased tissues (Lim et al, 2020). For example, using reduction mammoplasty samples and cells flow sorted based on CD49f/EpCAM, Nguyen et al identified three epithelial cell types in the normal breasts (Nguyen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations